Edukasi Literasi Keuangan Digital bagi Siswa Sekolah Dasar melalui Pengenalan Uang Elektronik dan Keamanan Bertransaksi - Tommy Kuncara; Nia Yuningsih; Budhi Sriyono Prasetyo; Eko Aprianto Nugroho; Abdul Muchlis (Jurnal Abdi Masyarakat Multidisiplin, 2026)
The development of digital payment systems has increasingly exposed elementary school students to electronic money cards, digital wallets, and QR-code payments through their families and everyday experiences. However, familiarity with payment technology is not always accompanied by an adequate understanding of digital balances, personal-data protection, and transaction security. This community service program aimed to improve elementary school students’ digital financial literacy through the introduction of electronic money and safe transaction practices. The program was conducted at SDN Margahayu XIII, Bekasi City, on June 15, 2026, involving 30 fifth-grade students. The program applied a Digital Financial Safety Lab model consisting of a diagnostic test, learning-station rotations, case-based games, balance-management exercises, confidential-information identification, and safe digital-transaction simulations. Evaluation was conducted using pre-tests and post-tests, student worksheets, performance assessments, and behavioral observations. The results showed that the students’ average digital financial literacy score increased from 48.2 in the pre-test to 88.3 in the post-test, representing an improvement of 40.1 points. The percentage of students achieving the minimum competency score increased from 13.3% to 93.3%, while 96.7% of participants demonstrated improved scores.